Advances in the Treatment Strategies in Hypertension: Present and Future - Paolo Verdecchia; Claudio Cavallini; Fabio Angeli (Journal of Cardiovascular Development and Disease, 2022)
Hypertension is the most frequent chronic and non-communicable disease all over the world, with about 1.5 billion affected individuals worldwide. Its impact is currently growing, particularly in low-income countries. Even in high-income countries, hypertension remains largely underdiagnosed and undertreated, with consequent low rates of blood pressure (BP) control. Notwithstanding the large number of clinical observational studies and randomized trials over the past four decades, it is sad to note that in the last few years there has been an impressive paucity of innovative studies. Research focused on BP mechanisms and novel antihypertensive drugs is slowing dramatically. The present review discusses some advances in the management of hypertensive patients, and could play a clinical role in the years to come. First, digital/health technology is expected to be increasingly used, although some crucial points remain (development of non-intrusive and clinically validated devices for ambulatory BP measurement, robust storing systems enabling rapid analysis of accrued data, physician-patient interactions, etc.). Second, several areas should be better outlined with regard to BP diagnosis and treatment targets. Third, from a therapeutic standpoint, existing antihypertensive drugs, which are generally effective and well tolerated, should be better used by exploiting available and novel free and fixed combinations. In particular, spironolactone and other mineral-corticoid receptor antagonists should be used more frequently to improve BP control. In particular, some drugs initially developed for conditions different from hypertension including heart failure and diabetes have demonstrated to lower BP significantly and should therefore be considered. Finally, renal artery denervation is another procedure that has proven effective in the management of hypertension.